Templation of a square grid copper(ii) 4, 4′-bipyridine network by a 3D PtS-related Cu(i)–Cu(ii) 4, 4′-bipyridine crystal. Issue 3 (10th November 2015) - Abrahams, C. T.; Abrahams, B. F.; Hudson, T. A.; Robson, R.
Abstract : Two topologically distinct Cu-4, 4′-bipyridine coordination polymers, sharing a similar geometric arrangement of Cu centres, are components of a composite crystal. Abstract : Two cationic networks, [Cu I Cu II (4, 4′bipy)4 (H2 O)2 ] 3+ and [Cu II (4, 4′bipy)2 (H2 O)2 ] 2+ have been formed from a solution in which Cu(i ) undergoes aerial oxidation. Whilst the topologies of the two networks are different the arrangement of Cu centres is almost identical, a structural feature which presumably allows for [Cu I Cu II (4, 4′bipy)4 (H2 O)2 ] 3+ to serve as a crystalline template for [Cu II (bipy)2 (H2 O)2 ] 2+ .